2020
DOI: 10.1111/tbed.13848
|View full text |Cite
|
Sign up to set email alerts
|

Screening virulence factors of porcine extraintestinal pathogenicEscherichia coli(an emerging pathotype) required for optimal growth in swine blood

Abstract: Porcine extraintestinal pathogenic Escherichia coli (ExPEC) is occurring with increasing frequency in China, which causes acute septicemia and sudden death in pigs leading to significant economic losses. Bacterial survival and even proliferation within host bloodstream are a common manifestation of a number of bacterial septicemias,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…It was further shown that Δ rfa displayed remarkable growth defects in fresh serum but not in heat-inactivated serum, indicating that lipopolysaccharides play important role in protecting ExPEC from being killed by heat-sensitive antimicrobial substances in serum, such as complements. The critical role of LPS biosynthesis in the resistance of serum killing has also been reported by other groups [ 9 , 69–71 ]. This could be attributed to the critical role of the LPS O-antigen in resistance to complement killing and hydrolysis of lysozyme [ 71 , 72 ].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…It was further shown that Δ rfa displayed remarkable growth defects in fresh serum but not in heat-inactivated serum, indicating that lipopolysaccharides play important role in protecting ExPEC from being killed by heat-sensitive antimicrobial substances in serum, such as complements. The critical role of LPS biosynthesis in the resistance of serum killing has also been reported by other groups [ 9 , 69–71 ]. This could be attributed to the critical role of the LPS O-antigen in resistance to complement killing and hydrolysis of lysozyme [ 71 , 72 ].…”
Section: Discussionsupporting
confidence: 72%
“…ExPEC is also a common bacterial pathogen in farm animals. Apart from the well-characterized avian pathogenic E. coli (APEC) that can cause multiple local and systemic infections in poultry which is one of the leading causes of morbidity and mortality [ 8 ], ExPEC in pigs has recently emerged as a fatal pathogen causing porcine meningitis, pneumonia, and septicemia, resulting in huge economic losses [ 9–11 ]. The incidence of ExPEC in pigs is reported to be increasing in recent years [ 11–13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial strains and plasmids used in this study were listed in Table S1 . PU-1 is an O2:K1 ExPEC strain (isolated from the blood of a piglet) causing acute sepsis in mouse infection model ( Ma et al., 2020 ; Ma et al., 2021 ). All strains were grown on Luria-Bertani (LB) broth medium at 37°C with 180 rpm, supplemented with corresponding antibiotics, or isopropyl–D-thiogalactopyranoside (IPTG) when necessary.…”
Section: Methodsmentioning
confidence: 99%
“…The type I pilus adhesin of ExPEC helps bacteria to colonize and invade the bladder epithelium [ 9 ]. ExPEC de novo nucleotide biosynthetic pathways allow bacteria to meet their metabolic requirements within host blood and promote bacterial growth in serum [ 10 ].…”
Section: Introductionmentioning
confidence: 99%